Application of Sweet Potato Flour in Bakery Products: Development, Sensory Evaluation, and Shelf-Life Stability (American Journal of Interdisciplinary Research and Innovation, 2025)
Adding sweet potato flour (Ipomoea batatas L.) to bakery products holds great promise for boosting their nutritional value and expanding food options, thanks to its abundance of carbohydrates, vitamins like provitamin A and vitamin A, dietary fibre, and essential minerals resources that are often overlooked despite sweet potatoes’ widespread availability worldwide. While many studies have tackled sweet potato processing and drying, we still lack a thorough look at how this flour performs in baked goods, particularly in terms of nutrition, sensory appeal, and how long products stay fresh. This research asks a key question: How does sweet potato flour, prepared with optimized osmotic dehydration or traditional drying, step in for part of the wheat flour to make breads, biscuits, and cakes that are more nutritious, tastier, and stable on the shelf compared to standard recipes? Our goal was to create these bakery items using local varieties of Local Sada and Kamala Sundari processed through osmotic dehydration (using 40–60% sucrose at 30–60°C) or conventional drying, then milled and blended into recipes replacing 10–45% of wheat flour. We analyzed the nutritional makeup, trained panels and consumers to evaluate taste and texture, and tested shelf life over four weeks, tracking moisture, microbial growth, and texture. This research revealed that foods made from sweet potato flour have noticeably higher levels of moisture, sugar and protein levels, as well as higher levels of dietary fibre without compromising sensory quality. For instance, they scored 6.85 ± 0.23 for the taste of Local Sada bread and 6.57 ± 0.11 for the taste of Kamala Sundari Bread. Shelf-life tests confirmed these items maintained good quality and microbial safety, making sweet potato flour a sustainable, nutrient-packed choice for healthier baked goods. This supports local farming and food security, offering food processors fresh, practical ideas for innovation. Our study fills a significant gap by combining processing, sensory, and stability insights in a new and actionable way.